First Application of An Efficient and Versatile Ligand for Copper-Catalyzed Cross-Coupling Reactions of Vinyl Halides with N-Heterocycles and Phenols - Kabir, M. Shahjahan (2010)
[Image: see text] 2-Pyridin-2-yl-1H-benzoimidazole L3 is presented as a new, efficient, and versatile bidentate N-donor ligand suitable for the copper-catalyzed formation of vinyl C-N and C-O bonds. This inexpensive and easily prepared ligand facilitates copper-catalyzed cross-coupling reactions of alkenyl bromides and iodides with N-heterocycles and phenols to afford the desired cross-coupled products in good to excellent yields with full retention of stereochemistry. This method is particularly noteworthy given its efficiency i.e., mild reaction conditions, low catalyst loading, simplicity, versatility, and exceptional level of functional group tolerance.